Potential Use of Remote Telesonography as a Transformational Technology in Underresourced and/or Remote Settings. (28th January 2013) - Pian, Linping; Gillman, Lawrence M.; McBeth, Paul B.; Xiao, Zhengwen; Ball, Chad G.; Blaivas, Michael; Hamilton, Douglas R.; Kirkpatrick, Andrew W.
Abstract : Mortality and morbidity from traumatic injury are twofold higher in rural compared to urban areas. Furthermore, the greater the distance a patient resides from an organized trauma system, the greater the likelihood of an adverse outcome. Delay in timely diagnosis and treatment contributes to this penalty, regardless of whether the inherent barriers are geographic, cultural, or socioeconomic. Since ultrasound is noninvasive, cost-effective, and portable, it is becoming increasingly useful for remote/underresourced (R/UR) settings to avoid lengthy patient travel to relatively inaccessible medical centers. Ultrasonography is a user-dependent, technical skill, and many, if not most, front-line care providers will not have this advanced training. This is particularly true if care is being provided by out-of-hospital, "nontraditional" providers. The human exploration of space has forced the utilization of information technology (IT) to allow remote experts to guide distant untrained care providers in point-of-care ultrasound to diagnose and manage both acute and chronic illness or injuries. This paradigm potentially brings advanced diagnostic imaging to any medical interaction in a setting with internet connectivity. This paper summarizes the current literature surrounding the development of teleultrasound as a transformational technology and its application to underresourced settings.